ʺCompliance as a tool for managing professional development of scientific and teaching staff of a community institution of higher educationʺ - Odarchenko, V. (Problems of Engineer-Pedagogical Education, 2024)
The article deals with the role of compliance as a mechanism for managing the professional development of research and teaching staff of a municipal higher education institution. The author theoretically analyzes the importance of compliance in managing the professional development of research and teaching staff of a municipal higher education institution. The key aspects of compliance in the context of managing the professional development of employees in the educational sector are investigated. The views of scientists on the definition of the concept of "compliance" are studied. It is theoretically proved that compliance is an important tool for managing the professional development of academic staff, especially in the current environment of increasing requirements for quality education and compliance with standards. The essence of the concept of "compliance" is considered through the prism of compliance with laws, regulations, procedures and ethical standards in the context of professional development management. The author of the article defines the functions of compliance such as: ensuring compliance with internal and external requirements, minimizing the risks of violation of legislation and standards. The paper examines modern practices of management and regulation of professional development of research and teaching staff of higher education institutions. The experience of applying compliance in the US educational system is studied. The article focuses on the influence of legislation, regulations and culture of compliance on the effectiveness of professional development management of higher education employees. The study proposes specific methods of professional development management, which may include the development of training programs, monitoring and evaluation of development results, as well as the introduction of mechanisms for stimulating and motivating employees. On the example of the organization of educational management in the Municipal Establishment "Kharkiv Humanitarian-Pedagogical Academy" of the Kharkiv Regional Council.